The Fading Art of Ritual Saba Dance Preserving Traditional Medical thru Mystical Skills - Abdullah Sani, Kamaluddin (2017)
This ritual dance can be seen in Ulu Terengganu, Terengganu, Malaysia. Saba‟ Dance history can first be tracked more than 150 years ago, and it was founded by Tok Shaman Smudge or Tok Bomoh Comot. During this period, the Saba Dance was performed for medical purposes such as treating diseases often related to mystical elements such as supernatural entities and entertainment. The legend related to this Saba was that Saba was a tree that grew in a garden filled with flowers in the sky. The garden was a place for the gods and goddesses to mix and play. Materials such as peak oil (Saba) which was used as the main ingredient, roasted, incense and filled with assorted tools spirit used in this dance. The dancers would perform dances around the tree Saba and they were accompanied by traditional music and sounds produced from bamboo called 'Bug'.. The dance is a combination of three forms of art; songs, music and dance. Traditional instruments such as the Child Threshold (bamboo), Children Cerating or Anak Cerating, tambourine (large drum) and flute (flute) made the orchestration of music, while songs were sung in contemporary verse. The dancers will dance to the embodiment of animals. Often these Games were held after the harvest, and also after recovering from any illness. This dance is believed to have existed in the state of Terengganu, situated in the coast of Peninsula Malaysia since the time of the religious transition Hindu – Buddhist – Islam archipelago of Circa 13 AD. Presentation will begin with incantations, perasap all musical instrument and then Red Duang Singer or the main character of this dance will swipe “children hermit”. Mohamed Najib (2009), referring to various factors that caused the erosion of traditional cultural activities, the culture of the present society is the main reason why there are fewer traditional arts activists around. Comparing this to the life in urban areas, the word „our‟ is rarely used as individualism, causing the diminishing of „Malay fraternity because the word refers to the gathering of Malay and when the Malays no longer gather among themselves, the culture and arts traditional activities would go away gradually. This paper will be focusing on it historical and restoration. As we all know, most of the Malay traditional dances are slowly becoming extinct. That is why we have to save and preserve all of them from becoming extinction. Indeed, as a Malay that lives in Malaysia and in Terengganu notably, the sense of pride of these Malay traditional dances especially traditional ritual dances should exist since it symbolizes the unique art and highest degree of creativity. Moreover, this research paper will also act as an effort towards the traditional dance restoration as well as the preserving of the Malay ritual dance that were nearly extinct.